3D Digital Clothing Design of Chu-style Lacquerware Patterns Based on Style3D Technology - Shijia Wang; Zhenzhen Zhang; Chen Yang (Textile & Leather Review)
This study investigates the application of Chu-style lacquerware patterns in modern clothing design using Style3D technology, aiming to explore innovative ways of integrating traditional cultural elements into contemporary fashion. By extracting and analysing the elements of animal, plant, and natural scenery motifs from Chu-style lacquerware, and utilising 3D digital technology for redesign and modelling, unique designs that blend traditional characteristics with modern fashion have been achieved. The results indicate that Style3D technology effectively enhances the visual presentation and production efficiency during the design process, offering new possibilities for the digital inheritance of traditional culture and personalised clothing customisation.